The Biochemical Properties of Some Species of Dicranum Hedw. - Demirbağ, Mustafa; Yıldırım, Vesile; Batan, Nevzat; Ökkeş,; Yılmaz, Okkes; Yilmaz,; Alataş, Mevlüt (My University, 2022)
In this study, the fatty acid compositions, lipid-soluble vitamins, sterols, flavonoids, and phenolic acid levels, as well as the DPPH radical scavenging activity of five different Dicranum species (D. majus, D. fuscencens, D. polysetum, D. scoparium and D. tauricum) were examined. While lipid-soluble vitamins, sterols, flavonoids, and phenolic acids were evaluated by HPLC, fatty acid compositions were assessed by gas chromatography. Based on study findings, it was determined that the examined Dicranum species exhibit low levels of flavonoids and lipid-soluble vitamins. However, it was seen that the species under study were high in terms of phenolic acids. Particularly, it was determined that the examined species have substantial levels of gallic acid (52.96-63.1 g/g) and vanilic acid (11.96-44.83 g/g). Cinnamic acid concentration was lowest in the examined samples. The radical scavenging capacity of the examined species was found to range from 48.92% to 86.89% in 250 µl in this study. Additionally, it was discovered that the investigated species' stigmasterol contents ranged from 35.3 to 46.05 g/g. The lowest levels of ergosterol and beta-sitosterol were discovered in D. majus and D. fuscescens. Based on the results of fatty acid composition, it was discovered that oleic acid (C18:1 n9), linoelic acid (C18:2 n6), and -linolenic acid (C18:3 n3) were the predominant unsaturated fatty acids and that palmitic acid (C16:0) and behenic acid (C22:0) was the major saturated fatty acid.
Keywords: Bryophyte; Dicranum; Biochemical Content